A STUDY OF AGREEMENT BETWEEN VISUAL INSPECTION WITH ACETIC ACID OF CERVIX AND PAP SMEAR FOR CERVICAL CANCER SCREENING - Ara, Chaman; Inayat, Kousar; Hanif, Asif; Afsar, Saba; Ullah, Ihsan (Journal of Ayub Medical College Abbottabad, 2019)
Background: One of the common causes of mortality and morbidity among young women is cervical cancer. Following a wash of cervix through acetic acid, the Papanicolaou (PAP) smears and the visual inspection with acetic acid (VIA), are compared. Objective of the study was to check the level of agreement between the PAP smear for cancer of cervix and VIA. Methods: It is a cross-sectional study and was carried out in Obstetrics and Gynaecology department, Sheikh Zaid Hospital, Lahore, Pakistan. All patients were put in lithotomy position and vaginal speculum was applied and pap smear taken followed by 5% acetic acid application to cervix and changes in the cervix noted down. Results: Patients with mean age 48±7.795 years were included. In 30 (12%) and 61 (24.4%) patients diagnosis of cervical cancer was positive on PAP smear and VIA respectively. The agreement between two test was significant with Kappa value = 0.322 and p-value ‰¤ 0.00. Conclusion: Our study revealed that agreement of PAP smear is almost 80%. VIA on the other hand can be used when there is no access to PAP smear. Keywords: Cervical cancer screening; Visual Inspection with acetic acid (VIA); Pap smear